Persepsi Guru Seni Budaya SMAN 1 Pangkalan Kuras Dalam Mengimplementasikan Kurikulum Merdeka - Della Agustia; Yahyar Erawati; Syefriani Syefriani (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
This research aims to determine the perceptions of arts and culture teachers at SMAN 1 Pangkalan Kuras in implementing the independent curriculum in Pangkalan Kuras, Pelalawan, Riau. Based on the results obtained in the field, it can be concluded that the author raised the Perceptions of Arts and Culture Teachers at SMAN 1 Pangkalan Kuras in Implementing the Merdeka Curriculum. The research used descriptive qualitative research methods. The objects of this research are: 1 Cultural Arts Teacher, Curriculum Representative, and 1 Student. The formulation of the problem in this research is: What is the perception of arts and culture teachers at SMAN 1 Pangkalan Kuras in implementing the independent curriculum? This research uses descriptive qualitative methods with data collection techniques by means of observation, interviews and documentation. The conclusions of this research are: 1. The arts and culture teacher at SMAN 1 Pangkalan Kuras has a positive perception of the implementation of the independent curriculum because the independent curriculum can increase motivation for the teacher and the independent curriculum is also very interesting to learn, 2. The arts and culture teacher at SMAN 1 Pangkalan Kuras has difficulty in designing teaching modules and the diversity of student opinions.